How do strategic actors think about the value of talent management? Moving from talent practice to the practice of talent. Issue 4 (7th November 2017) - Makram, Heba; Sparrow, Paul; Greasley, Kay
Abstract : Purpose: The purpose of this paper is to examine the perceptions of strategic actors in multinational organisations and to contribute to our understanding of how multinational companies articulate and define talent management and how – or what – they perceive its value to be. Design/methodology/approach: The paper is based on an empirical research study in which data were collected through 50 in-depth interviews across five multinational companies, conducted at a regional level across ten countries. Participants in the study were strategic actors representing two groups of managers/leaders (HR and talent management system designers and business leaders who are directly involved in the implementation of talent management). Findings: The absence of a formal talent management definition led to the emergence of different views and interpretations of what it is. It was viewed as a bundle, or set, of management ideologies manifested in all HR-related practices across four key areas: hiring the right talent, performance management, succession planning and development and retention. Performance management acted as the cornerstone. Talent management strategies displayed little participation for both system designers and implementers and distinct patterns of mystification, technologization and concretisation. The language of value was uncommonly used but provoked different ways of thinking about the role and meaning of talent management. Practical implications: The strategic actors in the talent system continue to see talent management in narrow functional and HR process terms. However, by bundling these HR functions and processes together, it is evident that they can be encouraged to recast their activity in a broader strategic narrative. Borrowing the notions and theories of value and value creation, and investigating talent management through this lens, should help to surface interesting insights into how talent management might be defined in practice, and how the language of value may in future be used to understand what talent management really is. Originality/value: The global study underpinning this paper attempts to deconstruct the understanding that strategic actors have about talent management from an empirical base. It contributes to the conceptual development of the talent management discourse by revealing the logics being pursued and address the definitional problem currently evidenced in the literature. It also provides direction for future research.